Demanda variável e produtividade em medicina diagnóstica: a experiência do cliente com o agendamento de exames - Martins, Leandro Ortigoza (2013)
The diagnostic medical services are perishable and the demand is variable. These are characteristics that struggle the maximization of results. Service providers traditionally offer exams through a scheduling system without overcoming, however, the inefficiency provoked by clients no-show. This study aims at investigating consumer satisfaction levels of the diagnostic medical services in relation to the operational model of scheduling, the acceptance to a new model with no scheduling need (free on demand) and analyzing three secondary dimensions common to the two models. The literature review embraced the historical evolution of the diagnostic medical services in Brazil, as well as the processes, opportunities and challenges associated with said development. It was verified that the existing relationship between perishability and seasonality jeopardizes company profitability due to the fact that it hinders a better use of the installed capacity, dilution of expenses and return on investment. The stage relative to the evolution of services and relationship marketing evidenced the importance of carrying out a survey with the own users of the services. Such research has a quantitative approach with a descriptive exploratory outline, and it was performed in 2.545 customers of a private company of diagnostic medical services in 2013. The data collection took place by applying a questionnaire and the following statistics techniques were adopted to assess the results: average comparisons, relationship between categorical variables (χ2), clusters building, factorial vectors and analysis of independent items. The results of the secondary dimensions (no show, seasonality and waiting time) have indicated that the subjects are engaged to avoid the no-show practice, trend to go to Establishments according to the present seasonality and are sensitive to waiting time. Pursuant to the main dimensions (scheduling and free on demand systems), it was detected different levels of acceptance, which may indicate in principle that the two systems are complementary and does not exclude each other. Therefore, it seems to be viable the adoption of a hybrid model in the referred operation, under which the offer of medical exams would occur through the use of the two systems so that customers could make their choice as preferred